COVID-19, Noncommunicable Diseases and Healthy Aging in Mexico - Pérez Rivera, Mayra (2021)
Introduction. The COVID-19 pandemic has unleashed the current situation of health systems and the health conditions of the population throughout the world. Objetive. Analyze the health conditions of the population in Mexico, especially in the 45 to 59 age group, and how non-communicable diseases and age are poor prognostic factors for COVID-19, showing healthy aging as an alternative to rethink public policies. Arguments for discussion. The age group from 45 to 59 years is required to be considered as a target group for the coverage of the Guaranteed Package of Health Services, whose actions are applied throughout the sector as preventive medicine actions, since it is currently included in a broader age group, taking into account the increase in mortality associated with age and comorbidity caused by the pandemic. Conclusions. Mexico requires a rethinking of the public policy of healthy aging, with the application of strategies and actions throughout the life course, seeking to apply urgent measures from the second half of life, starting at age 45, with secondary prevention actions of non-communicable diseases, since it is from this age and up to 79 years where the highest number of deaths has occurred in Mexico due to COVID-19, thus seeking to face the following pandemics with better health conditions of the population they come forward.